A meta-heuristic method to design off-grid community electrification projects with renewable energies. (15th December 2015) - Ranaboldo, Matteo; García-Villoria, Alberto; Ferrer-Martí, Laia; Pastor Moreno, Rafael
Abstract: The design of off-grid electrification projects considering hybrid systems and distribution microgrids is a complex task that requires the use of decision support tools. Most of existing tools focus on the design of hybrid systems without defining generator locations and microgrids configuration. Recently a deterministic heuristic was developed to solve the problem. In this study we present an enhanced deterministic heuristic and then a meta-heuristic procedure for designing community off-grid electrification projects based on renewable energies considering micro-scale resource variations and a combination of independent generation points and microgrids. Both new algorithms improve performance of the previous existing procedure. The new deterministic heuristic can rapidly (in a computational time lower than 1 min) obtain a good solution. On the other hand, the proposed meta-heuristic method considerably enhances solutions obtained by the deterministic heuristic with a computational time of 1 h on a standard PC. The improvement tends to raise as the complexity of the analyzed instance increases. The proposed algorithm is a complete design tool that can efficiently support the design of stand-alone community electrification projects requiring of low computational resources. Highlights: Two procedures are proposed to design community electrification projects. A fast deterministic algorithm and a meta-heuristic procedure are developed. Configurations with hybrid energy systems and micro-grids are considered. The proposed procedures enhance solutions obtained by the existing methods. The improvement is proportional to the complexity of the analyzed instance.